Prototheca-ID: a web-based application for molecular identification of Prototheca species. (13th November 2021) - Dziurzyński, Mikołaj; Decewicz, Przemyslaw; Iskra, Mateusz; Bakuła, Zofia; Jagielski, Tomasz
Abstract: The genus Prototheca houses unicellular, achlorophyllous, yeast-like algae, widely distributed in the environment. Protothecae are the only known plants that have repeatedly been reported to infect vertebrates, including humans. Although rare, protothecosis can be clinically demanding, with an unpredictable and treatment-resistant behavior. Accurate identification of Prototheca species relies upon DNA sequence-based typing of the mitochondrially encoded CYTB gene. However, no bioinformatic tool for the processing and analyzing of protothecal sequence data exists. Moreover, currently available sequence databases suffer from a limited number of records and lack of or flawed sequence annotations, making Prototheca identification challenging and often inconclusive. This report introduces the Prototheca-ID, a user-friendly, web-based application providing fast and reliable speciation of Prototheca isolates. In addition, the application offers the users the possibility of depositing their sequences and associated metadata in a fully open Prototheca-ID database, developed to enhance research integrity and quality in the field of Protothecae and protothecosis. Database URL : The Prototheca-ID application is available at https://prototheca-id.org